Denaturation of the principle of immediacy in drunk driving proceedings in the framework of virtual hearings - Justiniano Guerra, Adler Arquímedes (2022)
In drunk driving proceedings, the parties are empowered to reach the criterion of opportunity, the same which has well-established bases, which are immediacy, speed, concentration, among others. In the state of emergency (due to COVID-19) the form and manner of conducting hearings changed and began to be held virtually, with which the principle of immediacy with respect to the payment of compensation began to be denatured. Before this situation, the compensation was paid in the same act. Thus, it is necessary to delve into this point that not only affects the Corte Superior de Justicia de Huánuco [Court of Appeals in and for Huanuco], but all the courts of the country, since it generates unnecessary delays and an increased workload, since an agreement is never reached, becomes null and is submitted to oral trial.